YouTube’da Yayın Yapan Dijital Oyun Yayıncılarının İçeriklerine Dair İnceleme. - ARSLAN, Ayşe Mine; TAYDAŞ, Onur (Journal of Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The concept of game, which has become different with the developing and changing technology over time, has been replaced by digitalization in the 21st century. The digitalized game has taken its place in different mass media with the development of technology. Games played on phones and computers have started to spread to many masses around the world day by day, and this spread has evolved into commerce. So much so that the concept of "game publishing" has emerged on video content platforms such as YouTube. Publishers on this platform have started to produce game-related content on the channels they opened and to shoot informative videos for the audience about games such as "Minecraft" and "Roblox". Based on these definitions, it was felt necessary to research and examine the videos in the mentioned game category on YouTube. For this purpose, the study was concluded by scanning the necessary literature on the subject and conducting content analysis, which is a qualitative research method. The word cloud of the videos used in the study was created with the program called "MAXQDA" used in the content analysis, and the study was concluded with the results from the word cloud. As a result of the study, it was suggested that certain restrictions should be imposed on videos in the game category.